Clamor de Gaia: Violence, Ecology and Myth in Claribel Alegría - Fernández Zambudio, Josefa (2021)
In this paper, are shown the keys to the ways that Claribel Alegría approaches in her poetry the destruction of nature by men and of men among themselves, as specifications of the modes of violence. Here, will be analyzed the verses where these themes have been developed, in order to show which images, she has used and in which contexts she has expressed her concern, deepening his approach through some myths of the Greco-Roman tradition. These allow her to explore diverse perspectives, ranging from warning to hope for change, thanks to different metaphors and techniques of representation. It is shown that the poetic vision about the concern on how we connect with other people and with our environment is achieved thanks to the distancing provided by mythological character representations.